2009
DOI: 10.3354/dao02027
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR-based assay for quantitative detection of Hematodinium sp. in the blue crab Callinectes sapidus

Abstract: Hematodinium sp. is a parasitic dinoflagellate infecting the blue crab Callinectes sapidus and other crustaceans. PCR-based assays are currently being used to identify infections in crabs that would have been undetectable by traditional microscopic examination. We therefore sought to define the limits of quantitative PCR (qPCR) detection within the context of field collection protocols. We present a qPCR assay based on the Hematodinium sp. 18S rRNA gene that can detect 10 copies of the gene per reaction. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Similarly, we have found that the addition of BSA can counteract the inhibitory effects of remaining environmental inhibitors during diagnosis of Hematodinium using RT PCR. Thus, the use of BSA in the RT PCR protocol for diagnosis and quantification of Hematodinium in environmental samples is essential when inhibition is likely, as has been reported by others (Nagle et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, we have found that the addition of BSA can counteract the inhibitory effects of remaining environmental inhibitors during diagnosis of Hematodinium using RT PCR. Thus, the use of BSA in the RT PCR protocol for diagnosis and quantification of Hematodinium in environmental samples is essential when inhibition is likely, as has been reported by others (Nagle et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…(H.J. Small unpublished results), and based on an alignment of available SSU rRNA gene sequences, the primers developed by Nagle et al (2009) would also amplify the DNA of all Hematodinium and Hematodinium-like spp., as well as that of many other Syndiniales. As such, the above assays are genus-specific at best, but may also cross react with organisms in closely related genera.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The Qiagen DNeasy Blood and Tissue Kit, for example, has been shown to be very efficient (Bletz et al 2015) and could be used for future DNA extractions, but this would increase the cost and processing time of the assay considerably. Additionally, DNA extraction methods are unable to completely separate DNA from PCR inhibitors (Liu et al 2009, Nagle et al 2009). For this reason, dilutions were used in the PCR assays in order to decrease PCR inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous work of Nagel et al (2009), qPCR detection was used as an indicator of infection status in both hemolymph and muscle tissue. The ITS2 primer set and the protocol described in Hanif et al (2013) were used for all samples in this study.…”
Section: Quantitative Polymerase Chain Reactionmentioning
confidence: 99%